2021
DOI: 10.1094/phyto-11-20-0501-r
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Genomic Investigation of a Phytopathogenic Strain ofStenotrophomonas maltophilia

Abstract: Stenotrophomonas maltophilia is ubiquitous in diverse environmental habitats. It alerts significant concern due to its increasing incidence of nosocomial and community-acquired infection in immunocompromised patients and multiple drug resistance. It is rarely reported as a phytopathogen except causing white stripe disease of rice in India and postharvest fruit rot of Lanzhou Lily. Recently, Dickeya zeae and S. maltophilia strains were simultaneously isolated from soft rot leaves of Clivia miniata in Guangzhou,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Hu et al (2021) made a noteworthy discovery concerning S. maltophilia JZL strains. In contrast to typical phytopathogens like Dickeya zeae, these strains exhibited minimal production of plant cell walldegrading enzymes (CWDEs) but significantly higher levels of proteases.Additionally, compared to D. zeae, S. maltophilia strains demonstrated faster growth, produced more proteases, and formed extensive biofilm, especially on monocotyledonous hosts.…”
mentioning
confidence: 99%
“…Hu et al (2021) made a noteworthy discovery concerning S. maltophilia JZL strains. In contrast to typical phytopathogens like Dickeya zeae, these strains exhibited minimal production of plant cell walldegrading enzymes (CWDEs) but significantly higher levels of proteases.Additionally, compared to D. zeae, S. maltophilia strains demonstrated faster growth, produced more proteases, and formed extensive biofilm, especially on monocotyledonous hosts.…”
mentioning
confidence: 99%
“…Although SRP pathogens are frequently found to co-exist in the same fields ( Terta et al, 2010 ; Oulghazi et al, 2017 ; van der Wolf et al, 2017 ; Naas et al, 2018 ; Ozturk et al, 2018 ; Portier et al, 2019 ), so far there are only a few reported cases of co-infection ( Ge et al, 2021 ; Hu et al, 2021a ; Motyka-Pomagruk et al, 2021 ). In this study, LJ1 and LJ2 were isolated from the same soft rot taro corm; the two pathogens can infect taro both individually and together, although LJ2 caused more severe disease symptoms than LJ1 at 48-hpi ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether strains LJ1 and LJ2 promote or inhibit each other in planta, we measured the bacterial cell numbers by counting their corresponding colony-forming units (CFU) according to the method previously described ( Hu et al, 2021a ; Xue et al, 2021 ). Firstly, we visualized these two strains by, respectively, importing plasmids pBBP gdh (pmCherry) ( Liao et al, 2018 ) and pLAFR3-GFP (pGFP) ( Shi et al, 2019 ) into strains LJ1 and LJ2 by triparental mating with the help of E. coli HB101(RK2013).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we also isolated two bacterial pathogens from the same diseased rice sample, namely, Enterobacter asburiae and P. ananatis , both of which were determined as the causal agents of rice bacterial blight with no detectable synergistic or antagonistic interactions ( Xue et al, 2020 ). Moreover, Dickeya zeae and Stenotrophomonas maltophilia have been isolated from the same tissue of soft rot leaf of Clivia miniata with no synergism ( Hu et al, 2018 , 2021 ). These, and many other cases, all suggest the common phenomenon of co-infection of two or more pathogens on host plants in nature.…”
Section: Discussionmentioning
confidence: 99%